Effect of Estrogen on the Activity and Growth of Human Osteoclasts In Vitro - Fang-Ping Chen; Kun-Chuang Wang; Jing-Duan Huang (Elsevier, 2009)
Objective: Estrogen deficiency results in postmenopausal osteoporosis by increasing the rate of bone loss. The mechanism responsible for the effects of estrogen on osteoclasts is still unclear. Materials and Methods: The potential of mononuclear cells from cord blood or bone marrow to differentiate into mature osteoclasts when co-cultured with human osteoblast cells was investigated. The effects of estrogen on osteoclastogenesis and osteoclast activity were also examined. Results: Macrophage markers CD11b and CD14 were downregulated and vitronectin receptor was upregulated during 28 days' co-culture of mononuclear cells and human osteoblasts. Long-term co-culture resulted in the formation of numerous large tartrate-resistant acid phosphatase-positive multinucleated cells capable of resorption of bone slices. After incubation for 28 days, the addition of 17β-estradiol caused a significant decrease in the expression of vitronectin receptor and tartrate-resistant acid phosphatase-positive multinucleated cells in cultures derived from both bone marrow and cord blood. A significant decrease in bone resorption was also noted in the presence of estrogen. Conclusion: Estrogen not only suppresses osteoclastogenesis but also inhibits the activity of osteoclasts.